(untitled) (Asian Journal of Medical and Biological Research, 2016)
An experiment was conducted at the Soil Science Field Laboratory of Bangladesh Agricultural University, Mymensingh during boro season of 2014 to evaluate the effect of deep placement of nitrogen (N) fertilizers on N use efficiency and yield of BRRI dhan29 under flooded condition. The soil was silt loam in texture having pH 6.27, organic matter content 1.95%, total N 0.136%, available P 3.16 ppm, exchangeable K 0.095 me%, available S 10.5 ppm and EC 348 ?S cm-1. The experiment was laid out in a Randomized Complete Block Design (RCBD) with eight treatments and three replications. The treatments were T1 [Control], T2 [Prilled urea (130 kg N ha-1)], T3 [USG, 130 kg N ha-1], T4 [USG, 104 kg N ha-1], T5 [USG, 78 kg N ha-1], T6 [NPK briquette, 129 kg N ha-1], T7 [NPK briquette, 102 kg N ha-1] and T8 [NPK briquette, 78 kg N ha-1]. All the treatments except T6, T7 and T8 received 25 kg P and 64 kg K ha-1 as TSP and MoP respectively. In T6, T7 and T8 treatments, P and K were supplied from NPK briquettes. Prilled urea was applied in three equal splits. USG and NPK briquettes were applied at 10 DAT and were placed at 8-10 cm depth within four hills at alternate row. After deep placement of USG and NPK briquette, and each split application of PU, the water samples were collected for 5 consecutive days and analyzed for NH4-N concentration in surface water. After application of N fertilizers, the NH4-N in floodwater reached peak on the 2nd day in PU treated plots and then decreased rapidly over time. In the USG and NPK briquette treated plots, the NH4-N was generated slowly but spontaneously over the entire growth period as compared to PU indicating a beneficial role of USG and NPK briquette. The highest grain yield of 7.16 t ha-1 was recorded for T6 [NPK briquette, 129 kg N ha-1] which was statistically similar to that of T3 [USG, 130 kg N ha-1] and T4 [USG, 104 kg N ha-1]. The highest straw yield of 8.05 t ha-1 was obtained for T3 [USG, 130 kg N ha-1]. The deep placement of USG and NPK briquettes enhanced the recovery of applied N and N use efficiency in comparison with the broadcast application of N fertilizers. Asian J. Med. Biol. Res. June 2016, 2(2): 279-284